Total retroperitoneal lipectomy improves prognosis in patients with primary retroperitoneal liposarcoma: a comparative study - Gao, Haicheng; Liu, Shibo; Li, Wenjie; Zou, Boyuan; Miao, Chengli (Frontiers in Oncology, 2024)
BackgroundRetroperitoneal liposarcoma (RPLS) is the most common soft tissue sarcoma originating in the retroperitoneal space. Although surgery is the standard treatment, recurrence remains frequent. In this study, we aimed to explore the safety and efficacy of total (ipsilateral) retroperitoneal lipectomy (TRL) compared to traditional complete resection (CR) for primary RPLS.MethodsWe retrospectively analyzed patients with primary RPLS treated at our center between January 2014 and December 2020. Univariate and multivariable Cox regression analyses assessed the impact of demographic, operative, and clinicopathological variables on recurrence-free survival (RFS) and overall survival (OS). Kaplan-Meier plots illustrated RFS and OS, and the log-rank test compared time-to-event distributions.ResultsA total of 81 patients were included in the final analysis: 37 in the CR group and 44 in the TRL group. Demographic and clinicopathologic parameters were comparable between the two groups. Post-operative morbidity occurred in 30.9% of cases, with 15 (40.5%) in the CR group and 10 (22.7%) in the TRL group (P=0.086). There were 9 cases of severe complications at grade 3 or higher, with 5 cases in the CR group and 4 cases in the TRL group. There was no significant difference between the two groups (P=0.314). The TRL group demonstrated improved RFS and OS, particularly among dedifferentiated liposarcoma (DDLS) patients.ConclusionsTotal retroperitoneal lipectomy (TRL) appears to be a safe procedure that enhances survival outcomes in patients with primary RPLS. Further studies are needed to validate these findings.